EDUCATIONAL INTERVENTION ON EARLY MOBILIZATION COMPLIANCE AMONG POST-CESAREAN MOTHERS - Nurvitriana, Nidya Comdeca; Wijayanti, Karunia; Devi Maya (Journal of Medical Genetics and Clinical Biology, 2024)
Many mothers lack awareness of the benefits of early mobilization following caesarean section (post-Sc). This study aimed to assess the influence of educational intervention on early mobilization among post-Sc mothers at RSAD Level III Brawijaya Surabaya, utilizing a pre-experimental design with a single cohort. The sample consisted of 43 mothers who underwent caesarean section from December 2023 to January 2024, selected through purposive sampling. Early mobilization served as the dependent variable, with education as the independent variable. Results revealed a positive shift post-education, with 20 participants (47%) improving from the "good" category to only 2 (5%) post-education. Additionally, 22 respondents (51%) moved to the "sufficient" category, up from 19 (44%) previously. Conversely, the "less" category decreased from 22 (51%) to 1 (3%) post-education. Statistical analysis (ρ=0.001, α=0.05) confirmed significant impact of counseling on early mobilization post-caesarean section, rejecting H0. In conclusion, educational intervention positively affected maternal compliance with early mobilization after caesarean section at RSAD Level III Brawijaya Surabaya. Suggestions include integrating comprehensive early mobilization content into midwife education curriculum.